Examination of the impact of COVID-19 public health quarantine measures on acute mental health care services: A retrospective observational study. (August 2021) - Nejati, Nadine; Crocker, Candice; Kolajova, Miroslava; Morrison, Jason; Simon, Patryk; Sridharan, Sanjana; Tibbo, Philip
Abstract: This study assesses for the impact of Covid-19 public health quarantine measures on acute care psychiatric admissions, by comparing admission data from the quarantine period to a comparator period. A chart review was conducted for all admissions to an urban acute care psychiatric centre from Mar 22 – June 5 2020 (quarantine) and January 5 – Mar 21 2020 (comparator). Data was collected on the number of admissions, demographics, patients' psychiatric history, characteristics of admissions, discharge information, patients' substance use and social factors. Data was analyzed using a student's t-test for continuous variables and Chi squared analyses for categorical variables. Results demonstrated 185 admissions during quarantine and 190 during the comparator, with no significant differences in the distribution of admissions across time periods. There was a significantly greater frequency of admissions in the 35-44 age bracket and admissions involving substance use during quarantine. Additionally, admissions during quarantine were significantly shorter, with increased frequency of involuntary status and use of seclusion. The data suggests a vulnerability specific to individuals in their 30-40s during quarantine and demonstrates a need to better understand factors impacting this group. It also suggests that quarantine is associated with changes to substance use, potentiating high acuity illness requiring admission. Highlights: Covid-19 quarantine measures have implications for presentations of severe mental illness. Patients aged 35-44 may be disproportionately affected by quarantine measures. Changes in substance use during quarantine may potentiate severe mental illness. Further study of factors impacting mental illness during quarantine is required.